Keseimbangan mental dan spiritual: konsepsi enam kebutuhan zakiyah daradjat - Wati, Risma Elina (Maliki Interdisciplinary Journal, 2025)
Mental and spiritual balance is a crucial element of human existence, becoming increasingly important amidst complex emotional and social challenges. This paper aims to offer individuals, academics, and mental health professionals a practical understanding of how Zakiyah Daradjat’s Six Needs, which include love, security, self-esteem, freedom, success, and curiosity, can contribute to this balance. Findings and analysis indicate that fulfilling these needs not only supports psychological stability but also enhances one’s spiritual awareness. By fulfilling these needs, individuals will feel at ease when performing religious obligations and improve their self-confidence. Furthermore, this idea provides an important foundation for Islamic education and faith-based counseling, which help individuals achieve a balanced life in this world and the hereafter. This holistic approach is expected to improve the quality of life and overall happiness.